Lepromin-Induced Suppressor Cells in Patients with Leprosy - Vijay Mehra; Llewellyn H. Mason; James P. Fields; Barry R. Bloom (1979)
Abstract The possibility of an active mechanism of immunologic suppression in leprosy was explored by assessing the in vitro lymphocyte responses of 61 leprosy patients and 30 normal individuals to the mitogen Con A in the presence or absence of Dharmendra lepromin. Lepromin-induced suppression of Con A stimulation was found in 32 of 35 lepromatous patients and 15 of 15 borderline patients, but only 2 of 15 tuberculoid patients and 2 of 30 normal controls. Cell fractionation studies indicated at least two cell populations involved in the in vitro lepromin-induced suppressor activity, adherent cells and Tγ-cells.